Needs for Small Area Estimation: Perspectives From the US Private Forest Sector - Prisley, Steve; Bradley, Jeff; Clutter, Mike; Friedman, Suzy; Kempka, Dick; Rakestraw, Jim; Sonne Hall, Edie (Frontiers in Forests and Global Change, 2021)
The commercial forest sector in the US includes forest landowners and forest products manufacturers, as well as numerous service providers along the supply chain. Landowners (and contractors working for them) manage forestland in part for roundwood production, and manufacturers purchase roundwood as raw material for forest products including building products, paper products, wood pellets, and others. Both types of organizations need forest resource data for applications such as strategic planning, support for certification of sustainable forestry, analysis of timber supply, and assessment of forest carbon, biodiversity, or other ecosystem services. The geographic areas of interest vary widely but typically focus upon ownership blocks or manufacturing facilities and are frequently small enough that estimates from national forest inventory data have insufficient precision. Small area estimation has proven potential to combine field data from the national forest inventory with abundant sources of remotely sensed or other resource data to provide needed information with improved precision. Successful implementation of small area estimation by this sector will require cooperation and collaboration among federal and state government agencies and academic institutions and will require increased funding to further develop and implement the needed technologies.